BASIC/TRANSLATIONAL - G Protein-Coupled Receptor Biology 2011
DOI: 10.1210/endo-meetings.2011.part1.p8.p1-175
|View full text |Cite
|
Sign up to set email alerts
|

Retromer Terminates the Generation of cAMP by Internalized PTH Receptors

Abstract: Generation of cAMP by G protein-coupled receptors (GPCRs) and its termination is currently thought to occur exclusively at the plasma membrane of cells. Under existing models of receptor regulation, this signal is primarily restricted by desensitizationof the receptors through their binding to β-arrestins. However, this paradigm is not consistent with recent observations that the parathyroid hormone receptor type 1 (PTHR) continues to stimulate cAMP production even after receptor internalization, as β-arrestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
74
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 30 publications
9
74
1
Order By: Relevance
“…S1). Importantly, our previous studies showed that cAMP production induced by M-PTH(1-28) remains elevated for at least 30 min after ligand challenge (14).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…S1). Importantly, our previous studies showed that cAMP production induced by M-PTH(1-28) remains elevated for at least 30 min after ligand challenge (14).…”
Section: Resultsmentioning
confidence: 95%
“…For these assays, Gβγ CFP was expressed in HEK293 cells stably expressing HA-tagged PTHR (HA-PTHR), and cell lysates were prepared at different time points after a short exposure to either M-PTH(1-28) or M-PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), modified analogs of PTH that induce longer or shorter cAMP generation and biological responses, respectively (20). The difference in duration of cAMP signaling is thought to depend on the capacity of M-PTH(1-28), like PTH , to form an unusually persistent high-affinity complex with PTHR that is independent of G-protein coupling, whereas M-PTH(1-14) forms a more conventional high-affinity complex that is transient and dependent on G-protein coupling (2,20,21).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations